Microstructurally-based constitutive modelling of the skin – Linking intrinsic ageing to microstructural parameters. (7th May 2018) - Pond, D.; McBride, A.T.; Davids, L.M.; Reddy, B.D.; Limbert, G.
Highlights: A constitutive model for skin is proposed that links intrinsic ageing to parameter evolution. The model is motivated by mechanisms associated with microstructural evolution. The model captures both physical and geometric nonlinearities. The computational model is validated using published experimental data. Abstract: A multiphasic constitutive model of the skin that implicitly accounts for the process of intrinsic (i.e. chronological) ageing via variation of the constitutive parameters is proposed. The structurally-motivated constitutive formulation features distinct mechanical contributions from collagen and elastin fibres. The central hypothesis underpinning this study is that the effects of ageing on the mechanical properties of the tissue are directly linked to alterations in the microstructural characteristics of the collagen and elastin networks. Constitutive parameters in the model, corresponding to different ages, are identified from published experimental data on bulge tests of human skin. The numerical results demonstrate that degradation of the elastin meshwork and variations in anisotropy of the collagen network are plausible mechanisms to explain ageing in terms of macroscopic tissue stiffening. Whereas alterations in elastin affect the low-modulus region of the skin stress-strain curve, those related to collagen have an impact on the linear region.